Connectivity framework for rendezvous and mobile producer nodes using NDN interest flooding - Ahmed, Muhammed Zaharadeen; Hassan Abdalla Hashim, Aisha; Khalifa, Othman Omran; Saeed, Rashid Abdelhaleem; Alsaqour, Raed Ali; Alkali, Abdulkadir Hamidu (2021)
Named Data Networking is a promising application of Information Concentric Networking. More research is required to improve NDN mobility especially when Interest and Data contents are flooded during transmission. In named data networking framework, data integrity and security are highly guaranteed due to its nature of operation. Although, Information Concentric Networks are to some extend vulnerable to some form of Denial of Service (DoS) attacks. these attacks are mostly Interest Flooding Attacks. In this paper, a scalable solution that is capable of moderating complex interest flooding framework for rendezvous and producer nodes mobile routes is implemented by simulation. The simulation involves mobile producer (MP) transmission between the two interfaces (in-out bound) on a network. We further adopt the use an efficient protocol known as the Listen First Broadcast Later for Interest content as they are transmitted by consumer in search for data between nodes of producer and rendezvous in motion. Our implementation ensures preventing attackers at both ends of the links without affecting non attacking consumers and producers. The protocol depends on the mobile producer’s Data content reply and use a fix rate adaptation to initiate secured handoff. Simulation results in ndnSIM 2.1 and Wireshark present successful implementation of the producer to rendezvous scalable content delivery between the links.